Feasibility and sustainability evaluation of customary extraction methods of ginger bioactive compounds – A Review - Ayouaz, Siham; Fibri, Dwi Larasatie Nur; Madani, Khodir; Muhammad, Dimas Rahadian Aji (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— Zingiber officinale Roscoe (ginger) contains a high concentration of bioactive phytochemicals, which are desirable because of their important properties. The choice of suitable extraction methods is essential for practical applications of the bioactive compounds as it determine the properties of the extractable compounds. Several customary methods have been widely used by the scientists to extract the bioactive compounds of ginger. In this paper, a critical analysis of relative advantages and disadvantages was carried out for 6 types of extraction processes namely hydrodistillation, maceration, Soxhlet extraction, solvent-solvent extraction, decoction and infusion. This review discusses the different conventional methods, followed by a discussion of the importance of advancing the extraction techniques considering the environmental benefit and efficiency of the process. The application of innovative developed technologies is deemed environmentally beneficial, more efficient in terms of extraction yield and eliminate the issues connected with traditional extraction processes. The advanced extraction techniques discussed in this paper include microwave-assisted extraction, ultrasound-assisted extraction, enzyme-assisted extraction and supercritical fluid extraction. The technical data that are available in this review paper are beneficial for the scientist and the industry who work with ginger extraction. A clear direction of future studies is offered in this paper in which researchers must investigate the possibility of applying the advanced extraction method for retrieving bioactive compounds from ginger as well as study degrading effects of each new technique on phytochemical compounds and their metabolites intermediates.